2009
DOI: 10.4103/1596-3519.59577
|View full text |Cite
|
Sign up to set email alerts
|

Associations of advertisement-promotion-sponsorship-related factors with current cigarette smoking among in-school adolescents in Zambia

Abstract: Background: Tobacco use is the leading cause of noncommunicable disease morbidity and mortality. Most smokers initiate the smoking habit as adolescents or young adults. Methods: Survey data from the 2007 Lusaka (Zambia) Global Youth Tobacco Survey were used to estimate the prevalence of current cigarette smoking and assess whether exposure to pro-tobacco media and perception of the potential harm of secondhand smoke are associated with adolescents' smoking. Logistic regression analysis was used to estimate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…Smoking initiations in Ellisras rural boys starts between aged 11 to 12 and increases with increasing age. Similar results were reported in Hong Kong, Global Youth Tobacco Survey Project, Zambia and Cape Town for children between the age of 11 to 18 years or [28-31]. However, Damas et al [32] and Wen et al [33] reported that most smokers had parents (n = 111, 57%), as well as friends who smoked (n = 187, 96.4%).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Smoking initiations in Ellisras rural boys starts between aged 11 to 12 and increases with increasing age. Similar results were reported in Hong Kong, Global Youth Tobacco Survey Project, Zambia and Cape Town for children between the age of 11 to 18 years or [28-31]. However, Damas et al [32] and Wen et al [33] reported that most smokers had parents (n = 111, 57%), as well as friends who smoked (n = 187, 96.4%).…”
Section: Discussionsupporting
confidence: 75%
“…This was different from the 14.9% girls grade 8 to 11 and 5.2 to 7.5% girls aged 15 to 19 years reported in South Africa nationally [15,16]. However, the prevalence of smoking among the Ellisras boys was lower compared to that of the Zambian boys (9.3%) whereas smoking among the Zambian girls was high (12.1%) as compared to findings of both the current study and the national survey in South Africa [15,16,28]. …”
Section: Discussionsupporting
confidence: 38%
“…Both agenda-setting theory (McCombs and Shaw, 1993) and cultivation theory (Gerbner et al, 2002) posit that images in the media can change people’s perceptions about social reality and create “pictures in our heads” about the prevalence of behaviors, rituals, and customs. Evidence indicates the depiction of smoking in movies and other entertainment media, coverage of tobacco issues in news media, tobacco marketing and advertising, and tobacco control media all have an impact on smoking thoughts and behaviors (Dalton et al., 2009; DiFranza et al, 2006; Henriksen et al, 2010; Henriksen et al, 2002; Lovato et al, 2011; Morgenstern et al, 2011; National Cancer Institute, 2008; Song et al, 2007; Wakefield et al, 2003; Wakefield et al., 2006; Zulu et al, 2009). …”
Section: Social Exposure As Information Sources For Normsmentioning
confidence: 99%
“…It was not surprising that the prevalence of tobacco products usage increases with age increasing in the current sample [17]. Furthermore, the prevalence of tobacco products usage among the youth was not only increasing in South Africa but also to some African states like Zimabwe, Ghana, Zambia and Nigeria to name but a few [18,20-23]. The possible explanation could be that brand user imagery could be the major positioning strategy that advertisers used to create positive attitude to their brands, hence increasing the likelihood of purchase [7,24,25].…”
Section: Discussionmentioning
confidence: 96%
“…The extent at which the youth understand the danger of tobacco products on their lifestyles were also not covered in the study. Lastly, although exposure to tobacco products seems unlikely to affect youth’s understanding and the ultimate use [23,24] certainly, the exact wording of the advertisement of the tobacco products seen by the Ellisras rural youth could influence future use of the products which we did not cover in our study. However, this study provided valuable information on tobacco products promotion and knowledge in rural South African children and could be followed by an intervention study to remove this particular public health problem from rural South African communities.…”
Section: Discussionmentioning
confidence: 99%